O19.1 Preexposure prophylaxis of hiv (prep): utilisation estimates in australia. (13th September 2015) - Zablotska, I; Prestage, G; Grulich, AE
Abstract : Background: Preexposure prophylaxis (PrEP) with daily oral Truvada® is recommended for people at high risk for HIV infection. The population-level benefit of PrEP requires higher levels of use than is currently observed. In Australia, homosexually active men (HM), particularly those who identify as gay or homosexual, contribute most to HIV transmission. We estimated how many HM are eligible for and likely to request PrEP. Method: Using data from the Australian Bureau of Statistics (2013) and the second Australian Study of Health and Relationships (ASHR2, 2013), we estimated the number of HHMM nationally. PrEP eligibility was defined by the national PrEP guidelines. Input indicators from the 2013 Gay Community Periodic Surveys (GCPS) were applied to estimate the numbers of men eligible for PrEP based on each individual and any behavioural eligibility criteria. Using data from Treatment Options to Reduce Chances of HIV (TORCH) study, we estimated how many eligible HM are likely to request Truvada® for PrEP. Results: We estimated 143, 000 Australian men would identify as 'gay/homosexual' plus 95, 000 as 'other' HAM. In GCPS, 15.7% of the HIV non-positive respondents reported sustained risk behaviour (≥6 sex partners in previous 6 months). Overall, 5.7% of HIV non-positive respondents satisfied behavioural eligibility criteria for PrEP, while having at least one episode of receptive condomless anal intercourse in the previous 6 months appeared the most common criterion (5%). Based on national eligibility criteria, 8, 300 'gay/homosexual' and 5, 300 'other' HM can be considered eligible for daily PrEP in Australia, and 44.9% of those are likely to uptake PrEP. Conclusions: Our estimate of the number of HM eligible for PrEP in Australia is based on the current PrEP eligibility criteria, which target individuals at the highest risk for HIV infection. This estimation helps to predict service needed for PrEP prescribing nationally. Disclosure of interest statement: Input indicators for these analyses were obtained from Australian Bureau of Statistics, Australian Study of Health and Relationships and Gay Community Periodic Surveys (all funded by the Australian state and federal governments) and from Treatment Options to Reduce Chances of HIV (TORCH) study funded by Gilead Sciences. Funding sources were not involved in research conducted.